(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Water activity (aw) is a critical parameter in food science, directly affecting the safety, quality, and shelf life of food products. Unlike moisture content, which measures the total water present in a food product, water activity represents the availability of water for biological and chemical processes. This review explores the role of water activity in food stability, focusing on its influence on microbial growth, chemical reactions, and physical properties. By controlling water activity, food manufacturers can inhibit spoilage, extend shelf life, and maintain product quality. The discussion includes the impact of water activity on enzymatic activity, lipid oxidation, and Maillard browning, as well as its effects on the texture and structural integrity of food. Furthermore, the application of water activity in food processing, packaging, and regulatory compliance is examined. The review emphasizes the importance of understanding water activity as a tool for enhancing food stability, ensuring safety, and improving consumer satisfaction.